2018
DOI: 10.33546/bnj.516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fruit Decoction of Phaleria Macrocarpa on Uric Acid Levels in Elderly

Abstract: Background: The incidence of gout is rising both in the developed and developing countries not only in the elderly but also in young adults. Thus, the effort to reduce its incidence is necessary.Objective: To determine the effect of fruit decoction of phaleria macrocarpha on the levels of uric acid in the elderly.Methods: This was a pre-experimental study with pretest and posttetst design. This study was conducted at Sei Semayang Village North Sumatra from April to May 2017. There were 10 elderly selected usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Di Indonesia prevalensi asam urat tertinggi terjadi pada usia 75 tahun. Provinsi Aceh menempati urutan tertinggi kejadian asam urat, yaitu sekitar 13,3% dan prevalensi terendah terjadi di Provinsi Sulawesi Barat sekitar 3,2% dan rata-rata prevalensi penyakit sendi di indonesia sekitar 7,2 % (Simanullang, 2018).…”
Section: Pendahuluanunclassified
“…Di Indonesia prevalensi asam urat tertinggi terjadi pada usia 75 tahun. Provinsi Aceh menempati urutan tertinggi kejadian asam urat, yaitu sekitar 13,3% dan prevalensi terendah terjadi di Provinsi Sulawesi Barat sekitar 3,2% dan rata-rata prevalensi penyakit sendi di indonesia sekitar 7,2 % (Simanullang, 2018).…”
Section: Pendahuluanunclassified
“…Based on the results of a study conducted in Thailand, which was carried out from July 1999 to February 2000, from 1381 patients with gout, it was found that 18.4% of men and 7.8% of women had gout. While in China in 2011 the prevalence of increased uric acid levels was 21.6% in men and 8.6% in women (Simanullang, 2018).…”
Section: Introductionmentioning
confidence: 98%